2013
DOI: 10.1002/jmor.20182
|View full text |Cite
|
Sign up to set email alerts
|

Pigment cell mechanisms underlying dorsal color-pattern polymorphism in the japanese four-lined snake

Abstract: To provide histological foundation for studying the genetic mechanisms of color-pattern polymorphisms, we examined light reflectance profiles and cellular architectures of pigment cells that produced striped, nonstriped, and melanistic color patterns in the snake Elaphe quadrivirgata. Both, striped and nonstriped morphs, possessed the same set of epidermal melanophores and three types of dermal pigment cells (yellow xanthophores, iridescent iridophores, and black melanophores), but spatial variations in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 18 publications
1
45
0
Order By: Relevance
“…To characterize the pigment cell mechanisms of ontogenetic color pattern formation, we compared the number of epidermal melanophores, the proportion of dermal melanophores, and the vertical architecture of dermal pigment cells between juveniles (estimated in this study) and adult snakes (Kuriyama et al, ). In both the striped and nonstriped morphs, the number of epidermal melanophores and the proportion of dermal melanophores were higher in adult snakes than in juvenile snakes at the Nos.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To characterize the pigment cell mechanisms of ontogenetic color pattern formation, we compared the number of epidermal melanophores, the proportion of dermal melanophores, and the vertical architecture of dermal pigment cells between juveniles (estimated in this study) and adult snakes (Kuriyama et al, ). In both the striped and nonstriped morphs, the number of epidermal melanophores and the proportion of dermal melanophores were higher in adult snakes than in juvenile snakes at the Nos.…”
Section: Resultsmentioning
confidence: 99%
“…Kuriyama et al () concluded that changes in the densities of epidermal and dermal melanophores explain the observed variation in stripe vividness between the striped and nonstriped morphs. Our results were consistent with this inference and with the results of Murakami et al (); spatial variation in the abundance and architecture of epidermal and dermal melanophores is the key pigment‐cell mechanism that explains variation in stripe vividness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Japanese four‐lined snake Elaphe quadrivirgata has a naturally occurring body color polymorphism, including striped, pale‐striped, nonstriped, banded, and melanistic morphs (Mori, Tanaka, Moriguchi, & Hasegawa, ). Vivid striped and nonstriped morphs possess the same set of epidermal melanophores and dermal pigment cells (xanthophores at top, iridophores in middle, and melanophores in bottom), but vertical stratification of dermal pigment cells differs in different colored scales and the degree of spatial aggregation and concentrations of epidermal and dermal melanophores are the key determinants of stripe vividness in terms of sharpness of the boundary between dark‐ and light‐colored scales (Kuriyama et al, ). Even at the hatching, stripe and nonstripe patterns are detectable.…”
Section: Introductionmentioning
confidence: 99%